Successful parks for sharks: No-take marine reserve provides conservation benefits to endemic and threatened sharks off South Africa. (September 2021) - Albano, Patricia S.; Fallows, Chris; Fallows, Monique; Schuitema, Olivia; Bernard, Anthony T.F.; Sedgwick, Oliver; Hammerschlag, Neil
Abstract: Sharks are among the most threatened vertebrates on the planet. Marine protected areas (MPAs) have been widely established and promoted as a shark conservation tool. However, the geographic ranges of most imperiled shark species (endemic and threatened) fall outside the current global networks of MPAs, leaving the protective benefits of this tool questionable for the shark species of highest conservation concern. The Western Cape of South Africa is a hotspot for endemic and threatened shark species. Here, we examined the potential protective benefit of a no-take marine reserve (the De Hoop MPA) for imperiled shark species using baited remote underwater video stations (BRUVS). Eleven shark species were documented, with six of 11 species (55%) classified as threatened with extinction by the International Union for the Conservation of Nature. The composition of the shark assemblage was dominated by small to mid-sized species, including small endemics. Species-specific habitat preferences were identified, with all these habitats represented in the MPA. Frequency of occurrence and relative abundance of sharks on BRUVS were significantly higher inside the De Hoop MPA than outside. Both protected and commercially exploited sharks species exhibited higher relative abundance inside the MPA. Relative abundance also increased inside the MPA with increasing distance from the reserve boundaries. Our findings suggest that no-take MPAs can be an effective tool for protecting shark species of conservation concern, including threatened endemics, particularly if the MPA adequately incorporates their preferred habitats.